2004
DOI: 10.1038/nn1372
|View full text |Cite
|
Sign up to set email alerts
|

Natural oligomers of the amyloid-β protein specifically disrupt cognitive function

Abstract: A central unresolved problem in research on Alzheimer disease is the nature of the molecular entity causing dementia. Here we provide the first direct experimental evidence that a defined molecular species of the amyloid-beta protein interferes with cognitive function. Soluble oligomeric forms of amyloid-beta, including trimers and dimers, were both necessary and sufficient to disrupt learned behavior in a manner that was rapid, potent and transient; they produced impaired cognitive function without inducing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

62
1,342
6
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,600 publications
(1,421 citation statements)
references
References 45 publications
62
1,342
6
11
Order By: Relevance
“…The present observations suggest that prefibrillar A␤ 1-40 aggregates are more toxic than the mature fibrils, and have a dose-dependent effect. Our data are consistent with increasing evidence that small soluble oligomers, compared to mature fibrils, are likely the more toxic species of the peptides [10,11,19,35,38,42,69]. The moderate increase in toxicity with the higher amount of A␤ 1-40 mature fibrils is likely to be the result of minute amounts of residual prefibrillar aggregates in cell media, although a specific toxicity of the fibrils cannot be ruled out.…”
Section: Discussionsupporting
confidence: 90%
“…The present observations suggest that prefibrillar A␤ 1-40 aggregates are more toxic than the mature fibrils, and have a dose-dependent effect. Our data are consistent with increasing evidence that small soluble oligomers, compared to mature fibrils, are likely the more toxic species of the peptides [10,11,19,35,38,42,69]. The moderate increase in toxicity with the higher amount of A␤ 1-40 mature fibrils is likely to be the result of minute amounts of residual prefibrillar aggregates in cell media, although a specific toxicity of the fibrils cannot be ruled out.…”
Section: Discussionsupporting
confidence: 90%
“…However, increased Aβ oligomers after hCG treatment may have contributed to spatial memory deficits in rats as high concentrations of Aβ40 and Aβ42, particularly Aβ42, are considered to be neurotoxic and are correlated with cognitive deficits in AD (Naslund et al, 2000). Aβ oligomers are reported to disrupt long term potentiation (LTP) in vitro (Wang et al, 2002(Wang et al, , 2004 and in vivo (Walsh et al, 2002), and, appear to introduce memory impairment in AD mouse models (Cleary et al, 2004). In vitro research indicates that LH may increase Aβ by driving amyloid-β precursor protein (AβPP) processing to the amyoidogenic pathway (Bowen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A higher molecular weight Aβ oligomer (about 56 kDa) was purified from Tg2576 mice (an APP mutant mouse model of AD) and demonstrated to be toxic [34]. It was then found that naturally secreted oligomers (a mixture of trimers and dimers) can inhibit LTP in vivo [35] and disturb cognitive function in mice [35,36]. The toxic species of these "naturally secreted oligomers" was narrowed down to the "Aβ dimer" (based on its 8-kDa molecular weight), as that "Aβ dimer" isolated from AD brains is capable of impairing memory in mice [37].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%